Single-Domain Antibodies for Targeting, Detection, and In Vivo Imaging of Human CD4+ Cells - Traenkle, Bjoern; Kaiser, Philipp D.; Pezzana, Stefania; Richardson, Jennifer; Gramlich, Marius; Wagner, Teresa R.; Seyfried, Dominik; Weldle, Melissa; Holz, Stefanie; Parfyonova, Yana; Nueske, Stefan; Scholz, Armin M.; et al. (Frontiers in Immunology, 2021)
The advancement of new immunotherapies necessitates appropriate probes to monitor the presence and distribution of distinct immune cell populations. Considering the key role of CD4+ cells in regulating immunological processes, we generated novel single-domain antibodies [nanobodies (Nbs)] that specifically recognize human CD4. After in-depth analysis of their binding properties, recognized epitopes, and effects on T-cell proliferation, activation, and cytokine release, we selected CD4-specific Nbs that did not interfere with crucial T-cell processes in vitro and converted them into immune tracers for noninvasive molecular imaging. By optical imaging, we demonstrated the ability of a high-affinity CD4-Nb to specifically visualize CD4+ cells in vivo using a xenograft model. Furthermore, quantitative high-resolution immune positron emission tomography (immunoPET)/MR of a human CD4 knock-in mouse model showed rapid accumulation of 64Cu-radiolabeled CD4-Nb1 in CD4+ T cell-rich tissues. We propose that the CD4-Nbs presented here could serve as versatile probes for stratifying patients and monitoring individual immune responses during personalized immunotherapy in both cancer and inflammatory diseases.